Pelatihan Pengembangan Branding dan Pemasaran Produk Bubur Pedas Melalui Media Sosial dan Strategi Digital Marketing - Hermi Sularsih; Luh Dina Ekasari; Sri Indah (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
The prioritized issues in developing branding and marketing for Bubur Pedas (Spicy Porridge) micro, small, and medium enterprises (MSMEs) through social media and digital marketing strategies can be addressed gradually by adopting digital branding and marketing approaches. The implementation of sustainable programs, along with mentoring to establish business partnerships, plays a crucial role in this process. This study presents the execution of a Training on Branding and Marketing Development for Bubur Pedas Products through Social Media and Digital Marketing conducted by the Community Service Team, which received a positive response from Bubur Pedas MSMEs, represented by Kak Eva. The training results have significantly assisted the MSMEs in enhancing their product marketing by improving product quality through packaging design and effective marketing strategies on social media and digital platforms. Consequently, this training method proves to be both effective and efficient in enhancing the competitiveness of Bubur Pedas products from MSMEs.